Postcolonial endgame. Issue 1 (2nd January 2016) - Phillips, Mike
Abstract: This position paper assesses the present-day situation of black and Asian writers against that of earlier generations; the generation of post-war migrants and a second generation born or raised in Britain wrote under the pressures of postcolonial independence struggles and charged race relations in the former mother country. Whereas the writers of these generations could – out of necessity – develop alliances and a clearer sense of their own position as "black" or "Asian" writers in British society, the situation for non-white writers is more complex today in light of new identity choices, new kinds of migration and a fast-changing world. The article asks whether race still trumps ethnicity in the marketplace of ideas; how citizenship interacts with nationality and nationalism; and, if so, in what ways it affects the work of writers.